A quinta geração das comunicações móveis e a indústria 4.0: evolução, aplicações e desafios - AMORIM, Robson Carlos Castro (2024)
This paper presents a brief introduction on the evolution of the emergence of communications technologies and focuses its research on the development and evolution that culminated in the emergence of the fifth generation of mobile communications networks (5G), especially in the Brazilian scenario. This article makes a systematic review of the literature on the topic addressed, selecting the main findings about it, scientific publications and discusses the main results in the area, presenting a point of view on the implementation of the fifth generation in Brazil. After that, it makes an assessment and discussion about the implementation and what is expected for the scenario of industries 4.0, smart cities and internet of things (IoT) on the national scene. The article also evaluates the main implementation challenges and the advancement of national communications operators.